Acute hypoxia changes the gene expression profiles and alternative splicing landscape in gills of spotted sea bass (Lateolabrax maculatus) - Ren, Yuhang; Tian, Yuan; Mao, Xuebin; Wen, Haishen; Qi, Xin; Li, Jinku; Li, Jifang; Li, Yun (Frontiers in Marine Science, 2022)
Hypoxia is one of the most important environmental stressors in aquatic ecosystems. To deal with the hypoxia environment, fishes exhibit a series of physiological and molecular responses to maintain homeostasis and organism functions. In the present study, hypoxia-induced changes in gene expression profiles and alternative splicing (AS) events in spotted sea bass (Lateolabrax maculatus), a promising marine-culture fish species in China, were thoroughly investigated by RNA-Seq analysis. A total of 1,242, 1,487 and 1,762 differentially expressed genes (DEGs) were identified at 3 h, 6 h and 12 h in gills after hypoxia stress. Functional enrichment analysis by KEGG and GSEA demonstrated that HIF signal network system was significantly activated and cell cycle process was remarkably suppressed in response to hypoxia. According to the temporal gene expression profiles, six clusters were generated and protein-protein interaction (PPI) networks were constructed for the two clusters that enriched with hypoxia-induced (cluster 2) or -suppressed genes (cluster 5), respectively. Results showed that HIF signaling related genes including vegfa, igf1, edn1, cox2b, cxcr4b, ctnnb1, and slc2a1a, were recognized as hubs in cluster 2, while mcm2, chek1, pole, mcm5, pola1, and rfc4, that tightly related to cell cycle, were down-regulated and considered as hubs in cluster 5. Furthermore, a total of 410 differential alternative splicing (DAS) genes were identified after hypoxia, which were closely associated with spliceosome. Of them, 63 DAS genes also showed differentially expressed levels after hypoxia, suggesting that their expression changes might be regulated by AS mechanism. This study revealed the key biological pathways and AS events affected by hypoxia, which would help us to better understand the molecular mechanisms of hypoxia response in spotted sea bass and other fish species.